ANALISIS CURAHAN WAKTU KERJA WANITA PENGUSAHA AGROINDUSTRI MAKANAN SKALA RUMAH TANGGA DI KECAMATAN RENGAT KABUPATEN INDRAGIRI HULU - Hannum, Latipa; Maharani, Evy; Khaswarina, Shorea (Jurnal Online Mahasiswa (JOM) Bidang Pertanian, 2015)
The purpose of this research to analyse business woman’s working time on productive activity, reproductive activity and public social activity. This research held in Rengat district Indragiri Hulu regency. Research method used survey method. This research held on food agroindustry business woman's working time in the household scale in Rengat district with 30 respondents. The results showed, productive working hours of women-owned businesses in the District Rengat largely complies with the criteria of normal working hours, in which 18 women or (60%) of women entrepreneurs working below 160 hours/month, where as 12 women or (40% ) of women entrepreneurs have the outpouring of time that exceeds normal working hours. Business woman in Rengat district has productive activity’s working time was 4.479,17 hour/month (55%) from total woman’s working time, reproductive activity’s working time was 3.471,97 hour/month (42%) from total woman’s working time, public social activity’s working time was 224,50 hour/month (3%) from total woman’s working time, so based on business woman’s working time in Rengat district showed that more concentration on productive activity.     Keyword:  Working time, productive, reproductive and public social.